Edible Coating Application Based on Snail Shell Chitosan in the Effort to maintain the Quality and Storage of Tofu - Andi Artiningsih; Takdir syarif; Gusnawati; Febrian; Moh. Irsal Efendy (Postgraduate, University of Mataram, 2025)
Tofu also has a weakness, namely its high water content, so it is easily damaged because it is easily overgrown by microbes. Preservatives added are not limited to preservatives that are allowed, but many businessmen are naughty by adding formalin. White tofu is one that is circulating in the market. At room temperature the yower storage knows an average of 1-2 days. Efforts to preserve tofu by means of steaming and storing in a refrigerator can only preserve tofu for 1 day. This causes traders to commit fraud, one of which is preserving tofu so that it is durable, one of which is the addition of chemicals. According to the Food and Drug Supervisory Agency (BPOM). The treatment research method with the application of chitosan as an edible coating on white tofu is carried out in four stages, namely the preparation stage, immersion stage, storage stage, and testing stage. The preparation stage is carried nut by preparing all the materials and tools that will be used in the immersion, storage and testing stages. The immersion stage was done by soaking white tofu with concentrations varying of 0.5% The results of the long storage test for tofu coated with chitosan showed that the tofu soaked with chitosan solution with the addition 0.01 %.